PENGARUH GAYA KEPEMIMPINAN DAN SUASANA ORGANISASI TERHADAP BURNOUT DOSEN UNIVERSITAS TEKNOLOGI MATARAM - Henni Comala Hikmi; Agus Marjan Saputra; Rian Indranopa (Sekolah Tinggi Ilmu Ekonomi Nusantara Sangatta, 2026)
This study aims to determine and analyze the effect of leadership style and organizational climate on burnout among lecturers at Universitas Teknologi Mataram. This research uses a quantitative approach with an explanatory research design. The population consisted of lecturers at Universitas Teknologi Mataram, with a sample of 79 respondents selected using purposive sampling techniques. Data collection was carried out using questionnaires distributed directly to respondents. The analytical method used was multiple linear regression analysis assisted by SPSS software. The results showed that leadership style had a significant negative effect on lecturer burnout with a t-value of -3.217 and a significance value of 0.002. Organizational climate also had a significant negative effect on burnout with a t-value of -4.581 and a significance value of 0.000. Simultaneously, leadership style and organizational climate significantly affected burnout with an F-value of 38.624 and a significance value of 0.000. The coefficient of determination (R²) was 0.504, indicating that 50.4% of lecturer burnout could be explained by leadership style and organizational climate.